Pendampingan Pengembangan Media Pembelajaran Berbantuan Virtual Reality bagi Guru di Kabupaten Lebak - Guntara, Yudi; Kriswahyudi, Bambang; Harisudin, Ahmad; Safitri, Alda; Kristiaji, Darmawan; Fitri, Amelia Febriana; Astari, Rana Putri (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2022)
The demands of today's teachers must have skills in using technology as an effective teaching tool. However, the availability of facilities and infrastructure was an obstacle for teachers to apply technology, especially virtual reality in the learning process. Therefore, the Department of Physics Education, Untirta, Banten collaborated with the teacher assosication at Lebak Regency to provide training on the development of virtual reality assisted learning media for teachers at Lebak Regency. The methods used are presentation, discussion, demonstration and practicum. The results of this service show that 90% of teachers can create virtual physics classrooms using Millea lab and can be operated properly.